A trimeric tri-Tb3+ including antimonotungstate and its Eu3+/Tb3+/Dy3+/Gd3+-codoped species with luminescence properties. Issue 35 (27th August 2020) - Xu, Xin; Lu, Changtong; Xie, Saisai; Chen, Lijuan; Zhao, Junwei
Abstract : A trimeric tri-Tb 3+ -including antimonotungstate and its Eu 3+ /Tb 3+ /Dy 3+ /Gd 3+ -codoped species were prepared and their photoluminescence behaviors and energy transfer interactions were studied. Abstract : A trimeric tri-Tb 3+ -including antimonotungstate (AMT) hybrid Na17 (WO4 )[Tb(H2 O)(Ac)(B-α-SbW9 O31 (OH)2 )]3 ·50H2 O (Tb3 W28 ) was successfully synthesized, in which the capped tetrahedral WO4 group plays a significant template role in directing the aggregation of three [B-α-SbW9 O33 ] 9− fragments and three Tb 3+ ions. Eu 3+ /Tb 3+ /Dy 3+ /Gd 3+ -codoped AMT materials based on Tb3 W28 were firstly prepared and their luminescence properties were investigated. The red emitter Eu 3+, yellow emitter Dy 3+, and nonluminous Gd 3+ ions were codoped into Tb3 W28 to substitute Tb 3+ ions for investigating the energy transfer (ET) mechanism among Eu 3+, Tb 3+, and Dy 3+ ions. Upon the 6 H15/2 → 4 I13/2 excitation at 389 nm of the Dy 3+ ion, the ET1 mechanism (Dy 3+ → Tb 3+ ) was confirmed as a non-radiative dipole–dipole interaction. Under the 7 F6 → 5 L10 excitation at 370 nm of the Tb 3+ ion, the ET2 mechanism (Tb 3+ → Eu 3+ ) was identified as a non-radiative quadrupole–quadrupole interaction. Under excitation at 389 nm, the two-step successive Dy 3+ → Tb 3+ → Eu 3+ ET3 process was proved in Dy1.2 Tb3 z Eu0.03 Gd1.77−3 z W28 . Through changing the excitation wavelengths, the emission color of Dy1.2 Tb1.2 Eu0.03 Gd0.57 W28 can vary from blue to yellow, in which a near-white-light emission case was observed upon excitation at 378 nm. This work not only provides a systematic ET mechanism study of hetero-Ln-codoped AMTs, but also offers some useful guidance for designing novel performance-oriented Ln-codoped polyoxometalate-based materials.